Impact of SGLT-2 inhibitors on modifiable cardiovascular risk factors in Romanian patients with type 2 diabetes mellitus - Adriana Gherbon; Mirela Frandes; Darius Dîrpeş; Romulus Timar; Bogdan Timar (Diabetology & Metabolic Syndrome, 2024)
Abstract Background Modifiable cardiovascular risk factors are high blood pressure, smoking, diabetes, sedentary lifestyle, obesity, and hypercholesterolemia. Aim To investigate the impact of sodium-glucose 2 co-transporter inhibitors (SGLT-2i) on modifiable cardiovascular risk factors in Romanian patients diagnosed with type 2 diabetes mellitus (T2DM). Method A retrospective study was conducted on 200 Romanian patients with T2DM who were being treated with SGLT-2i, either Dapagliflozin or Empagliflozin. Collected data included demographic characteristics, such as weight, body mass index (BMI), fasting blood glucose (FBG), creatinine, glycated hemoglobin (HbA1c), abdominal circumference (AC), urine albumin-to‐creatinine ratio (UACR), systolic blood pressure (SBP), diastolic blood pressure (DBP), C-reactive protein (CRP) and N-terminal pro b-type natriuretic peptide (NT-proBNP). The patients were observed for one year after being treated with SGLT-2i. Results The mean value of FBG decreased from 180.00 mg% (IQR: 154.50–207.00) to 130.00 mg% (IQR: 117.50–150.00) (p < 0.001), and the mean of HbA1c values decreased from 8.40% (IQR: 7.98-9.15%) to 7.30% (IQR: 6.90-7.95%) (p < 0.001). We also obtained significant positive effects on body weight, i.e., the weight decreased from 90.50 kg (82.00-106.50) to 89.00 kg (77.50–100.00) (p = 0.018), BMI from 32.87 kg/m2 (29.24–36.45) to 31.00 kg/m2 (27.74–34.71) (p < 0.001) and AC from 107.05 (± 16.39) to 102.50 (± 15.11) (p = 0.042). The UACR decreased from 23.98 mg/g (19.76–36.85) to 19.39 mg/g (1.30-24.29) (p < 0.001). Initially, the median value for SBP was 140.00mmgHg (130.00-160.00), and for DBP was 80.00 mmgHg (72.00–90.00), and one year after treatment, the medium value was 120.00 mmgHg (115.50–130.00) for SBP (p < 0.001), and 72.00 mmgHg (70.00–78.00) for DBP (p < 0.001) The mean CRP values decreased from 68.00 mg/dL (56.25–80.25) to 34.00 mg/dL (28.12–40.12) (p < 0.001), and the mean NT-proBNP decreased from 146.00pg/mL (122.50-170.50) to 136.00 pg/mL (112.50-160.50) (p = 0.005). Conclusion Treatment with SGLT-2i in Romanian patients with T2DM has beneficial effects on modifiable cardiovascular risk factors.